Gender, sexuality and Islam in contemporary Indonesia: queer Muslims and their allies - Garcia Rodriguez, Diego (Routledge, Taylor & Francis, 2024)
"Gender, Sexuality and Islam in Contemporary Indonesia explores gender, sexuality and religion in contemporary Indonesia. It is the first book-length analysis of the experiences of queer Muslims in Indonesia, the largest Muslim country and the world's fourth most populous nation, as well as the first monograph exploring the voices of their allies vis-à-vis the role of Indonesian progressive Islam and Islam Nusantara. An ethnographic study based on semi-structured in-depth interviews, participant observation and media analysis, the book analyses how queer Indonesian Muslims come to, and navigate, their gender, sexual and religious subjectivities and subject positions, beliefs and practices. This is done by paying attention to their interactions with family, education, media, and peers. It also investigates the emergence of queer religious geographies through the case of an annual camp leading to alternative discussions on gender, sexuality, and religion impacting processes of subjectivity formation among participants. The author draws on recent scholarship that attends to 'agency' not merely as a synonym for resistance but also as a modality of action to examine the rise of queer religious agentic systems through the everyday practices of queer Muslims. Finally, the book explores the background of the allies of queer Muslims who have come to develop queer-inclusive strategies from within Islam by considering the processes that shaped their advocacy and the role of Islam Nusantara. The book reflects on the critical role of Islam for gender and sexual minorities in Indonesia. Presenting the voices, practices and activism of present-day Indonesians to explore the position of Islam as a source of emotional strength, guidance, and social support, this book will be of interest to researchers in the fields of Gender and Sexuality Studies, Religious Studies, Asian Studies and Southeast Asian Studies, Islamic Studies and Queer Anthropology"--